Bidirectional role of reactive oxygen species during inflammasome activation in acrolein-induced human EAhy926 cells pyroptosis. (22nd November 2021) - Jiang, Liping; Luo, Songsong; Qiu, Tianming; Li, Qiannan; Jiang, Chunteng; Sun, Xiance; Yang, Guang; Zhang, Cong; Liu, Xiaofang; Jiang, Lijie
Abstract: Acrolein, a known toxin in tobacco smoke, has been demonstrated to be associated with inflammatory cardiovascular diseases, such as atherosclerosis. However, the definite mechanism of acrolein-induced inflammation remains unclear. Here, we report that acrolein induces reactive oxygen species (ROS) production in EAhy926 cells. Additionally, acrolein induces EAhy926 cells' inflammatory response and pyroptosis by activating NOD-like receptor protein 3 (NLRP3) inflammasome. Also, acrolein-induced cytotoxicity could be attenuated by N-acetyl-L-cysteine (NAC). Furthermore, acrolein upregulates the level of autophagy which can be reversed by NAC. Notably, the present study also indicates that autophagy inhibited by inhibitor 3-methyladenine (3MA) and siAtg7 exacerbate acrolein-induced NLRP3 inflammasome activation and pyroptosis. In summary, acrolein induced cytotoxicity by ROS-mediated NLRP3 inflammasome activation, and ROS upregulates the level of autophagy to inhibit the NLRP3 inflammasome excessive activation, indicating the bidirectional role of ROS in acrolein-induced cellular inflammation. Our results may provide novel mechanistic insights into acrolein-induced cardiovascular toxicity.